Driving Fitness in Different Forms of Dementia: An Update. Issue 10 (6th August 2019) - Toepper, Max; Falkenstein, Michael
Abstract : BACKGROUND/OBJECTIVES: Most forms of dementia are associated with progressive cognitive and noncognitive impairments that can severely affect fitness to drive. Whether safe driving is still possible in the single case, however, is often difficult to decide and may be dependent on both severity and type of the respective dementia syndrome. Particularly in early disease stages, Alzheimer disease dementia (ADD) and different types of non‐Alzheimer dementias, such as vascular dementia (VaD), frontotemporal dementia (FTD), dementia with Lewy bodies (DLB), and Parkinson disease dementia (PDD), might differentially affect fitness to drive. DESIGN: To examine the effects of severity and type of dementia on driving fitness, we conducted a systematic review with qualitative narrative synthesis, involving different driving outcomes in different forms and stages of dementia. SETTING: Literature research included MEDLINE and PsycINFO databases with a focus on the most relevant and recent publications on the topic. PARTICIPANTS: The population of interest included older drivers in different stages of ADD and different forms of non‐Alzheimer dementias (VaD, FTD, DLB, and PDD). MEASUREMENTS: Narrative description of driving outcomes in the population of interest. RESULTS: Overall, previous studies suggest that driving fitness is severely impaired in moderate and severe dementia, irrespective of the type of dementia. In milder disease stages, fitness to drive appears to be more severely impaired in non‐Alzheimer dementias than in ADD, since the non‐Alzheimer syndromes are not only associated with driving‐relevant cognitive but noncognitive risk factors, such as behavioral or motor symptoms. CONCLUSIONS: Based on these findings, practical recommendations are presented, including a risk evaluation for driving safety, depending on severity and type of different dementia syndromes. J Am Geriatr Soc 67:2186–2192, 2019